Handbook of Learning from Multiple Representations and Perspectives - Van Meter, Peggy; LIST, ALEXANDRA; Lombardi, Doug; KENDEOU, PANAYIOTA (Taylor & Francis, 2020)
The Role of Validation in Integrating Multiple Perspectives, Handbook of Learning from Multiple Representations and Perspectives, Tobias Richter, Hannes Münchow, Johanna Abendroth, validity, two-step model, beliefs, comprehension, integration, multiple texts, text comprehension, digital learning, knowledge creation, componential information, conflicting information